2018
DOI: 10.7494/geol.2018.44.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Potential source rocks in the Ropianka Formation of the Magura Nappe (Outer Carpathians, Poland) – geochemical and foraminiferal case study

Abstract: Abstract:To optimize exploration for new hydrocarbon accumulations in the Polish Outer Carpathians, it is necessary to concentrate attention on identification of hydrocarbon accumulations of the "shale-gas" type. Results of recently completed analysis suggested new such possible targets in the Magura Basin, preserved in the Outer Carpathian Magura Nappe. Analysis of the preliminary results of paleoenvironmental and geochemical studies of these shales is the subject of this paper. Micropaleontological and geoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Bubík et al (1999) (1960) from Mora via. The common occurrence of Caudammina excelsa was noticed in the Magura Nappe from Lower Paleocene deposits (Waśkowska et al 2018), from Campanian-Maastrichtian (Malata 2002) and from Maastrichtian-Lower Paleocene deposits (Malata et al 1996). Olszewska (1980) and Bąk (2004) indi cate similar asemblages from other Outer Carpa thian areas.…”
Section: Complexmentioning
confidence: 84%
See 2 more Smart Citations
“…Bubík et al (1999) (1960) from Mora via. The common occurrence of Caudammina excelsa was noticed in the Magura Nappe from Lower Paleocene deposits (Waśkowska et al 2018), from Campanian-Maastrichtian (Malata 2002) and from Maastrichtian-Lower Paleocene deposits (Malata et al 1996). Olszewska (1980) and Bąk (2004) indi cate similar asemblages from other Outer Carpa thian areas.…”
Section: Complexmentioning
confidence: 84%
“…Hanzlíková (1983) draws attention to the stratigraphic significance of Placentammina pla centa and described the Placentammina placenta dominated assemblages from the Moravian Paleo cene. Beckmann et al (1982) and Waśkowska et al (2018) found assemblages rich in these taxa in the Paleocene, whereas Geroch (1960) and Bąk (2004) Samples taken from the thin-bedded complex between the Biotite Sandstone and Shale and the Mutne Sandstone Member (complex II) contain rich and diversified assemblages. Taking into account the occurrence of biostratigraphical markers, they refer to the upper part of Rzehakina inclusa Zone of Early Maastrichtian-Maastrichtian/Paleocene age.…”
Section: Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The foraminiferal as sem blages of the Farony Shale cor respond to the as sem blages from the Cre ta ceous part of the Ropianka and Jaworzynka for ma tions of the Magura Nappe. As sem blages with nu mer ous Caudammina gigantea (acme assem blages) were no ticed ear lier by Blaicher (1958), Sikora and ¯ytko (1960), Bieda et al (1963), Jednorowska (1966, 1975, Geroch et al (1967), Malata (1981Malata ( , 2002, Malata and Oszczypko (1996), Oszczypko et al (1990Oszczypko et al ( , 2005, Stráník et al (2000), Waoekowska (2021), Waoekowska et al (2021), in creased numbers of Caudammina ovulum (Grzybowski) with nu mer ous Caudammina gigantea Geroch were de scribed by Sikora and ¯ytko (1960), Malata (1981) and Oszczypko et al (2005), and Saccammina-Placentammina rich as sem blages were no ticed by Jednorowska (1968) and Waoekowska et al (2018Waoekowska et al ( , 2021. The spe cies found in the Farony Shale are truly cos mo pol i tan, and as seen in a re cent study of DWAF from an IODP site in the Tas man Sea (Kaminski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It can be a pre rog a tive to be long to the same fa cies. In the sam ple, 21/FAR-2/20 Cau dammina excelsa (Dyl¹¿anka) is pres ent, which is an other fea ture of the Placentammina-Saccammina acme (Waoekowska et al, 2018;Waoekowska, 2021).…”
Section: Age Analysismentioning
confidence: 99%